2021
DOI: 10.17516/1997-1389-0364
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of the Downstream Process for Polyhydroxyalkanoate Copolymer P(HB‑co-HHx) Extraction with Nonhalogenated Solvents

Abstract: Biobased and biodegradable polyhydroxyalkanoates (PHAs) are promising alternatives to common plastics. Due to their high production costs, only a minimal share of global plastic production is composed of PHA. A major contributor to the high costs minimizing the potential to occupy a larger market share is the downstream process. To obtain high recovery yields and pure products, most approaches rely on large amounts of solvents. While short-chain-length PHA (scl-PHA) is poorly soluble in nonhalogenated solvents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Nevertheless, it is anticipated that the influence of residual lipids is neglectable when a non‐halogenated solvent‐based downstream processing is applied, which was shown for high‐purity P(HB‐ co ‐HHx) recovery from R . eutropha cells grown on plant oil and waste animal fat (Riedel et al, 2013 ; Thiele et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is anticipated that the influence of residual lipids is neglectable when a non‐halogenated solvent‐based downstream processing is applied, which was shown for high‐purity P(HB‐ co ‐HHx) recovery from R . eutropha cells grown on plant oil and waste animal fat (Riedel et al, 2013 ; Thiele et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…We showed that the bacteria efficiently take up the substrate, and an optimized C/N ratio will allow no residual lipids that potentially interfere with the downstream. Nevertheless, it is anticipated that the influence of residual lipids is neglectable when a non-halogenated solvent-based downstream processing is applied, which was shown for high-purity P(HB-co-HHx) recovery from R. eutropha cells grown on plant oil and waste animal fat (Riedel et al, 2013;Thiele et al, 2021).…”
Section: Bioreactor Cultivationsmentioning
confidence: 99%
“…Molecular weight distribution of the PHA polymers was determined by size exclusion chromatography (SEC) from CDW samples as described previously ( Thiele et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%